2011
DOI: 10.1007/s12195-011-0161-3
|View full text |Cite
|
Sign up to set email alerts
|

Live Cell Imaging of Src/FAK Signaling by FRET

Abstract: The Src/FAK complex is involved in many signaling pathways and plays crucial roles in cell adhesion/migration. It becomes clear that the subcellular localization of Src and FAK is crucial for their activities and functions. In this article, we first overview the molecular mechanisms and functions of Src and FAK involved in cell adhesion/migration. We then introduce the development of genetically encoded biosensors based on fluorescence resonance energy transfer (FRET) to visualize the activities of Src and FAK… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
16
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(17 citation statements)
references
References 57 publications
(90 reference statements)
1
16
0
Order By: Relevance
“…The Src and FAK family kinases were shown to regulate actin cytoskeleton reorganization (58,59); therefore, the importance of these molecules in R. montanensis invasion of tick cells was examined in this study. As shown in Fig.…”
Section: Fig 3 Arp2/3 Complex Is Important For Rickettsial Internalizmentioning
confidence: 99%
“…The Src and FAK family kinases were shown to regulate actin cytoskeleton reorganization (58,59); therefore, the importance of these molecules in R. montanensis invasion of tick cells was examined in this study. As shown in Fig.…”
Section: Fig 3 Arp2/3 Complex Is Important For Rickettsial Internalizmentioning
confidence: 99%
“…The authors demonstrated that Src was activated upon integrin ligation using fibronectin‐coated beads and that this depended upon intact actin and microtubule cytoskeletons. This probe has subsequently been used in other studies to analyse activation of Src during cell adhesion and migration in a number of contexts (reviewed in Seong et al , ).…”
Section: Use Of Single‐chain Fret Biosensors To Study Signalling Durimentioning
confidence: 99%
“…Focal adhesion kinase (FAK) is a non-receptor tyrosine kinase consisting of a FERM domain (protein 4.1, ezrin, radixin and moesin homology), a kinase domain, and a FAT domain (targeting focal adhesion (Seong et al, 2011a). Phosphorylation of FAK at Tyr397 leads its binding to Src kinase, and then regulates many signaling molecules such as PI3K, Grb7 and Rho GTPases (Zhao et al, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…The activity of FAK is directly related to its subcellular localization (Seong et al, 2011a). It not only exists in the cytoplasm, but also targets focal adhesion through its carboxyl-terminal FAT region (Lee et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation